Ethical consideration in program evaluation for health professional education programs - Farrukh, Khadija (Journal of the Pakistan Medical Association, 2024)
Objectives: To explore the ethical considerations and measures of quality assurance during data-collection for programme evaluation in health professional education. Method: The qualitative case study was conducted at Bahria University of Health Sciences, Karachi, from August to November 2023, and comprised faculty members involved in programme evaluation for at least two years having done a minimum two audit cycles. System thinking philosophical framework was used during the data-collection phase. A diverse sample was selected to ensure representation from different sectors and roles within the teams. Data was collected through participant observation, semi-structured interviews and focus group discussions. Data was subjected to thematic analysis. Results: There were 7 faculty members who were interviewed individually twice in addition to 4 focus group discussion. Members of quality assurance team were experts in their respective fields, but were not found to be well-versed in terms of ethical considerations that should guide data-collection. This lack of knowledge may inadvertently lead to ethical lapses in the evaluation process. Another ethical challenge seen was bias in the data-collection phase. Conclusion: Faculty members integral to programme evaluation efforts were found to lack knowledge regarding ethical considerations in data-collection, which can pose significant risks. Key Words: Programme evaluation, Ethics, Health professional education.